Pengaruh Media Roda Putar Terhadap Kemampuan Mengenal Pola Dan Motorik Halus Anak Usia Dini - Nur Fadhilah; Mustaji Mustaji; Miftakhul Jannah (Jayapangus Press, 2021)
This study aims to determine the effect of rotating wheel media on the ability to recognize patterns in group A children in Kindergarten, Waru Sidoarjo sub-district. This type of research is experimental research using a quasi-experimental design. The variables in this study consisted of the independent variable rotating wheel media (X) and the dependent variable the ability to recognize patterns (Y1) and children's fine motor skills (Y2). The samples in this study were 40 children of the experimental group (19 children of Al Muslim Kindergarten A-1 and 21 children of TK Parlaungan A-1) and 40 children of the control group (19 children of Al Muslim Kindergarten A-2 and 21 children of TK Parlaungan A-2) . The data analysis technique in this study used parametric statistics independent t-test test. The results showed that (1) there was an effect of rotating wheel media on the ability to recognize patterns in group A children in Kindergarten, Waru Sidoarjo district, statistically the t value = 2.862 with a significant level of p = 0.007 less than 5%; (2) There is an effect of rotating wheel media on the fine motor skills of group A children in Kindergarten, Waru Sidoarjo sub-district, statistically the value of t = 4,534, the significant level of p = 0.000 is less than 5%.